REPRESENTASI DINAMIKA SOSIAL DALAM NASKAH DRAMA “RT NOL RW NOL”: TEORI KONFLIK RALF DAHRENDORF - Nurizkya, Azhara (University of Brawijaya, 2026)
The absurd drama “RT Nol RW Nol” by Iwan Simatupang represents social chaos through its depiction of the lives of a community of homeless people living under a bridge. This work serves as a mirror of the reality of inequality and marginalization in society. This article aims to analyze the representation of social dynamics, particularly structural conflict, as manifested in the drama script. This study uses Ralf Dahrendorf's Conflict Theory as an analytical framework to unravel the power relations between the ruling class and the oppressed class. The results of the study show that systematic conflict is represented through the concept of “forced association” that unites marginalized people, interactions that reinforce hierarchy, and symbolic spatial settings. The imperative class (the state through the police and bureaucracy, as well as capital owners) controls and oppresses the subordinate class (the homeless) through repressive mechanisms, administrative rules, and stigmatization. Although various forms of resistance emerge, the conflict is continuous and unresolved, which in fact becomes a source of dynamics as well as sharp social criticism of a system that fails to humanize its marginalized citizens.